Deciphering the roles of the constitutive androstane receptor in energy metabolism - Yan Jiong; Chen Baian; Lu Jing; Xie Wen (Acta Pharmacologica Sinica; Vol 36, No 1 (January 2015): Acta Pharmacologica Sinica(Special Feature:Nuclear Receptors: Biology, Structures, and Drug Discovery）, 2017)
The constitutive androstane receptor (CAR) is initially defined as a xenobiotic nuclear receptor that protects the liver from injury. Detoxification of damaging chemicals is achieved by CAR-mediated induction of drug-metabolizing enzymes and transporters. More recent research has implicated CAR in energy metabolism, suggesting a therapeutic potential for CAR in metabolic diseases, such as type 2 diabetes and obesity. A better understanding of the mechanisms by which CAR regulates energy metabolism will allow us to take advantage of its effectiveness while avoiding its side effects. This review summarizes the current progress on the regulation of CAR nuclear translocation, upstream modulators of CAR activity, and the crosstalk between CAR and other transcriptional factors, with the aim of elucidating how CAR regulates glucose and lipid metabolism.